Students’ Need Analysis on Methods Used By Lecturers in Teaching English For Management Studies - Rachel Rachel; Sushy Teko Patanduk; Abedneigo Carter Rambulangi (Universitas Cokroaminoto Palopo, 2021)
This study was aimed at exploring the students’ need on methods used by lecturers in teaching English for management studies. The type of research used to achieve the above objective is descriptive quantitative. The data was collected through questionnaires that was given to students, lecturers, and graduates through google form, and it was analyzed by using Likert Scale. The total respondents was 72. They consist of 4 lecturers, 17 graduates, and 51 students. Result of the research indicates that the eight methods are important to be applied in teaching ESP. This means that lecturer can combine these methods as they are needed by the students at Management Study Program at UKI Toraja.